Protocol of a cluster randomised controlled trial evaluating the effectiveness of an online parenting intervention for promoting oral health of 2–6 years old Australian children. Issue 10 (13th October 2022) - Tadakamadla, Santosh Kumar; Rathore, Vatsna; Mitchell, Amy E; Johnson, Newell; Morawska, Alina
Abstract : Introduction: Dental decay is a major problem among Australian children. It can be prevented through good self-care and limiting sugar intake, but many parents/caregivers lack the skills and confidence to help their children adopt these practices. This trial will evaluate the efficacy of Healthy Habits Triple P - Oral health, a web-based online programme, in improving children's oral health-related behaviours (toothbrushing, snacking practices and dental visits) and related parenting practices, thereby preventing dental caries. Methods and analysis: This is a cluster, parallel-group, single-blinded, randomised controlled trial of an online intervention for parents/caregivers of children aged 2–6 years. From the City of Gold Coast (Australia), 18 childcare centres will be randomly selected, with equal numbers randomised into intervention and control arms. Intervention arm parents/caregivers will receive access to a web-based parenting intervention while those in the control arm will be directed to oral health-related information published by Australian oral health agencies. After the completion of the study, the Healthy Habits Triple P - Oral health intervention will be offered to parents/caregivers in the control arm. The primary outcome of this trial is toothbrushing frequency, which will be assessed via Bluetooth supported smart toothbrushes and parent/caregiver report. Data on other outcomes: parenting practices and child behaviour during toothbrushing, consumption of sugar rich foods and parents' confidence in dealing with children's demands for sugar rich food, and dental visiting practices, will be collected through a self-administered questionnaire at baseline (before randomisation), and 6 weeks (primary endpoint), 6 months and 12 months after randomisation. Data on dental caries will be collected at baseline, 12 and 18 months post-randomisation. Ethics and dissemination: Ethical approval has been obtained from Human Research Ethics Committees of Griffith University (2020/700) and the University of Queensland (2020002839). Findings will be submitted for publication in leading international peer-reviewed journals. Trial registration number: ACTRN12621000566831.